2018
DOI: 10.3390/nu10020148
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Digital Marketing of Unhealthy Commodities on Young People: A Systematic Review

Abstract: The marketing of unhealthy commodities through traditional media is known to impact consumers’ product attitudes and behaviors. Less is known about the impacts of digital marketing (online promotional activities), especially among young people who have a strong online presence. This review systematically assesses the relationship between digital marketing and young people’s attitudes and behaviors towards unhealthy commodities. Literature was identified in June 2017 by searches in six electronic databases. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 49 publications
2
101
0
3
Order By: Relevance
“…40,41 Celebrity endorsements that appear more natural or authentic (such as a picture of an endorser using a branded product in an activity of daily life as one might see on social media), have also been shown to yield higher persuasive effects than that of traditional forms of endorsement (eg, television commercial). 42 Studies also suggest that young people may have more difficulty recognizing digital marketing. 42 Studies also suggest that young people may have more difficulty recognizing digital marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Celebrity endorsements that appear more natural or authentic (such as a picture of an endorser using a branded product in an activity of daily life as one might see on social media), have also been shown to yield higher persuasive effects than that of traditional forms of endorsement (eg, television commercial). 42 Studies also suggest that young people may have more difficulty recognizing digital marketing. 42 Studies also suggest that young people may have more difficulty recognizing digital marketing.…”
Section: Discussionmentioning
confidence: 99%
“…39 As for peer endorsement, such as "sharing" or "liking" branded content on social media, a recent systematic review concluded that this form of marketing may influence young people more than advertisements sponsored by companies. 42 Studies also suggest that young people may have more difficulty recognizing digital marketing. [43][44][45] This is concerning because the recognition of advertising is considered the first step in protecting oneself against its persuasive intent.…”
Section: Discussionmentioning
confidence: 99%
“…Advertising online, including food marketing, targets adolescents specifically, drawing successfully on their social-developmental needs for connection with peers, working under the radar to activate emotional, identity-laden responses and build long-lasting relationships with brands [ 35 , 36 , 71 , 72 , 73 ]. Buchanan and colleagues [ 74 ] note that “earned” social media advertising (forwarded by users within networks—see Box 1 ) is believed to have the most detrimental effects on young consumers, as this form of marketing is no longer clearly commercial, and can be disguised as a post by the user. Indeed, industry data suggest that “native” advertising (particularly when delivered within social media news feeds) generates positive reactions compared to more overt forms of display advertising, resulting in a 28% increase in advertising viewed on mobile devices and a greater subconscious reaction [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most research on food marketing still focuses on traditional broadcast media, there has been some momentum towards researching digital food marketing in recent years. This includes a systematic review on digital marketing and youth attitudes and behaviour related to unhealthy commodities (food, alcohol and tobacco) by Buchanan et al 19 and reports by the WHO. 20 21 In summary, these reviews and reports, along with individual studies, have identified the potential of digital technology for health promotion interventions, through dietary and physical activity mobile apps for selfmonitoring, among others.…”
Section: Open Accessmentioning
confidence: 99%